2005
DOI: 10.1002/eqe.463
|View full text |Cite
|
Sign up to set email alerts
|

On the inelastic seismic response of asymmetric buildings under bi-axial excitation

Abstract: SUMMARYThe elastic and inelastic seismic response of plan-asymmetric regular multi-storey steel-frame buildings has been investigated under bi-directional horizontal ground motions. Symmetric variants of these buildings were designed according to Eurocodes 3 and 8. Asymmetric buildings were created by assuming a mass eccentricity in each of the two principal directions. The torsional response in the elastic and inelastic range is qualitatively similar with the exception of the sti edge in the strong direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 7 publications
2
23
1
Order By: Relevance
“…This complicated phenomenon specific to asymmetric structures has also been reported by others previously (e.g. Marušić and Fajfar, 2005). Moreover, Tables 5 and 6 demonstrate that the SSF reduces as the plan eccentricities increases.…”
Section: Discussionsupporting
confidence: 57%
“…This complicated phenomenon specific to asymmetric structures has also been reported by others previously (e.g. Marušić and Fajfar, 2005). Moreover, Tables 5 and 6 demonstrate that the SSF reduces as the plan eccentricities increases.…”
Section: Discussionsupporting
confidence: 57%
“…to regular (along the height) structures with lateral load-carrying elements having similar deformation shapes (all frames or all walls). It is encouraging that in a companion study on such multi-storey buildings [3] very similar ÿndings were obtained, although the global characteristics of the structural system and the loading were very di erent. Moreover, the main ÿndings were conÿrmed also in a study made for a realistic 3-storey reinforced concrete building with sti ness and strength eccentricity [4].…”
Section: Discussionmentioning
confidence: 58%
“…Although extensive parametric studies have been performed (only some of them are presented in this paper), and a very simple single-storey structural model was used, it was possible to explore only a very limited number of cases. Nevertheless, together with the companion paper [3], several combinations of input parameters have been I. PERU Ä S AND P. FAJFAR investigated and some consistent trends have been observed. Based on the results of these studies, the following conclusions, important for the development of simpliÿed procedures, can be drawn:…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Currently, the available investigations primarily concentrate on the dynamic analysis of these regularly asymmetrical multistorey buildings. Marus ić et al [15] studied the elastic and inelastic seismic response of a multistorey regular eccentric steel frame structure under bidirectional earthquake motions. They found that the reduction in lateral stiffness due to plastic deformations in a certain direction may considerably influence the lateral load-resisting member in the orthogonal direction.…”
Section: Introductionmentioning
confidence: 99%